THE IMPACT OF COVID-19 OUTBREAK ON INDONESIA TOURISM STOCK PERFORMANCE - Farah Amalia (Jurnal Industri Parawisata, 2022)
The Corona Virus Disease (Covid-19) Outbreak weakened the country’s economy all around the world. The tourism industry suffered the most, experiencing the highest stock price decline within a year of the Covid-19 outbreak. The purpose of the study is to examine whether COVID-19 has a significant effect on stock price movements of the Indonesian tourism industry in general and how the capital market reacts to the Covid-19 outbreak in Indonesia in particular. The study used event-study approach and t-statistical to test the hypothesis. The result showed that on and after the day of announcement of COVID-19 outbreak, eighty four percent of Indonesia tourism stocks showed significantly negative cumulative abnormal returns, indicating a significant impact of the Covid-19 outbreak on tourism stock performance. Empirical findings could be used to make investment decision and estimate future winner investment sector for the similar pandemic.